2009
DOI: 10.1002/pd.2327
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of right aortic arch: associated findings, pregnancy outcome, and clinical significance of vascular rings

Abstract: RAA can be accurately diagnosed by fetal echocardiography. The outlook for these patients largely depends on the presence of associated defects, mainly CHDs, and their severity. If isolated, aortic arch anomalies are asymptomatic vascular variants in most cases. This information is important to assist parental counseling in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
103
2
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 19 publications
15
103
2
17
Order By: Relevance
“…Almost all studies showed an overall good rate with regard to the selection and comparability of the study groups and for the ascertainment of the outcome of interest. The main weaknesses of these studies were their small sample size, being series from high-risk populations, Bronshtein (1998) 6 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) Bronshtein (1998) 6 Patel (2006) 10 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon ( Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon (2014) and lack of ascertainment of all individual outcomes. Furthermore, most studies had a relatively short period of follow-up after birth.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studies showed an overall good rate with regard to the selection and comparability of the study groups and for the ascertainment of the outcome of interest. The main weaknesses of these studies were their small sample size, being series from high-risk populations, Bronshtein (1998) 6 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) Bronshtein (1998) 6 Patel (2006) 10 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon ( Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Miranda (2014) 28 Razon (2014) and lack of ascertainment of all individual outcomes. Furthermore, most studies had a relatively short period of follow-up after birth.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Another two had mild symptoms, which improved. Computed tomographic angiography and barium swallow at 2 and 5 years of age showed no significant obstruction Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Chaoui (2002) 25 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Bronshtein (2011) 30 Gul (2012) 29 Miranda (2014) 28 Razon (2014) 24 Current study Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Bronshtein (1998) 6 Gul (2012) 29 Miranda (2014) 28 Achiron (2002) 2 Patel (2006) 10 Berg (2006) 8 Zidere (2006) 7 Tuo (2009) 9 Galindo (2009) 11 Turan (2009) 12 Hsu (2011) 32 Li (2011) 31 Bronshtein (2011) 30 Chaoui (2002) 25 Gul (2012) …”
Section: Cohort Studymentioning
confidence: 99%
“…but the minimal risk of chromosomal anomalies in fetuses with isolated right aortic arch anomalies may justify not performing invasive testing. 19) In case 6, fetal karyotyping and FISH test were performed due to TOF detected via sonographic findings. The results of FISH analysis confirmed 22q11.2 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Bu varyasyonlar, embriyonik farengeal ark'ın bir veya birden fazla komponentinin anormal gelişiminin sonucu olup genellikle beş grupta incelenir. Bunlar çift ark, sağ arkus aorta ile birlikte ayna görüntüsü dallanması, sağ arkus aorta ile birlikte anormal dallanma, sol arkus aorta ile birlikte anormal dallanma ve servikal arkus aortadır Arkus aorta anomalileri erişkin popülasyonun %0,1'inde görülür 8,9 ve opere edilen konjenital kardiyovasküler defektlerin %1'inden azını oluşturur 6 . Bu anomaliler genellikle saptanamadığı için gerçek insidansları tam olarak bilinmemektedir.…”
Section: Tartıșmaunclassified
“…Kardiyak ve ekstrakardiyak defektler eşlik ediyorsa, arkus aorta anomalileri varlığında 22q11 delesyon artışı ve konjenital kalp hastalığı ile birliktelik şansları arasında yakın ilişki olduğu bildirilmiştir 6,12 . McElhinney ve arkadaşlarının yaptığı bir çalışmada 22q11 delesyonu olanların %24'ünde sağ arkus aorta veya çift arkus aorta görüldüğü bildirilmiştir 10 .…”
Section: Tartıșmaunclassified